Considering the Nature of Science Content Knowledge and Pedagogical Content Knowledge in Canadian Science Education Programs: An Environmental Scan - Ellen Watson; Sarah Ragoub (Journal of Teaching and Learning)
Ellen Watson holds a PhD in Secondary Education from the University of Alberta. She is an assistant professor in the Department of Curriculum of Pedagogy at the Brandon University Faculty of Education where she teaches science teacher education courses, general education courses, and graduate courses in curriculum. Her research interests include science teacher education, science teacher epistemic beliefs, development of epistemic beliefs, and physics education. Ellen is currently serving as the past president of the Science Education Research Group, a special interest group of the Canadian Society for the Study of Education.